Customizing a Coordinative Crab Molecule BCP‐3N with Multifunctionality for High‐Performance Inverted Perovskite Solar Cells. Issue 9 (24th July 2022) - Wang, Gaopeng; Xu, Rongguo; Zhu, Hong; Li, Yu; Liu, Tongfa; Lin, Zedong; Hu, Mingyu; Xing, Zhou; Gao, Jiali; Yang, Shihe
Abstract : Defects at the perovskite grain boundaries and the interfaces between perovskite and charge transport layers in perovskite solar cells (PSCs) are a curse of nonradiative recombination losses and device degradation channels. Herein, the custom design and synthesis of a multifunctional small molecule ( N 2, N 9 ‐bis(3‐(dimethylamino)propyl)‐4, 7‐diphenyl‐1, 10‐phenanthroline‐2, 9‐dicarboxamide (BCP‐3N) featured by the π‐conjugated phenanthroline and an array of lone‐pair electron donor atoms from the carbonyl and amine groups are reported. The BCP‐3N is used as a Lewis base to multidentate passivate the undercoordinated Pb 2+ ions forming an ultrathin tunnel layer, in synergy with ethanol as a green antisolvent to simultaneously orient the growth of perovskite, resulting in a significantly reduced defect density in perovskite films. With BCP‐3N, a significant increase in open‐circuit voltage ( V oc  = 1.12 V) is achieved of inverted (p–i–n structure) PSCs, along with a record power conversion efficiency of ≈21% among alcohol antisolvent processed cells. Also, attested are a much higher illumination and humidity stability of the BCP‐3N‐based device. Combined experimental and theoretical studies have uncovered the multifunctional roles of BCP‐3N in stabilizing high‐quality Cs–FA–MA triple‐cation mixed perovskites under light, bias, and humidity stresses, enlightening the molecular design for PSCs. Abstract : The crab‐shape molecule named BCP‐3N is synthesized to chelate with insufficiently coordinated Pb ions in perovskite films. In synergy with the green antisolvent ethanol (EtOH) to orient the growth of perovskite, the internal stability and power conversion efficiency (PCE) of inverted perovskite solar cells are simultaneously improved, with a record PCE of 20.98% using alcohol as polar antisolvent.